Polemik dan Tantangan Penegakan Hukum Progresif di Indonesia - M. Syafi'ie (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Satjipto Rahardjo progressive laws have the basic idea that the law is for man, not vice versa. The law does not exist for itself but for something broader, that is for human dignity, happiness, prosperity and glory of man. Second, the law is not an institution that final, because the law is always in the process to continue to be. Therefore, the law does not inevitably invite progressive polemic against the wall and the legal system is structurally in Indonesia. Polemic is one of them is misguided thinking Satjipto Rahardjo charges in view of legal science. Satjipto Rahardjo accused of removing the identity of jurisprudence based on a logical theoretical framework (order of logic), where the true measure of the coherence standard, namely the correspondence between the idea that one with another idea that forms a unity of ideas. Satjipto thinking instead of thinking of jurisprudence, but because the idea of social science framework used is an empirical theory framework (order of fact), which measures the standards of truth correspondence, namely the similarity between the idea and reality. However, in the middle of the polemic, though progressive laws are challenged to find its form, in the midst of the people who do not believe in legal positivism, and in many cases are in the vacuum space and suppressing.